Recent Advances in Sensing Applications of Molecularly Imprinted Photonic Crystals - Fan, Jing; Qiu, Lili; Qiao, Yu; Xue, Min; Dong, Xiao; Meng, Zihui (Frontiers in Chemistry, 2021)
Photonic crystals (PhCs) with bright structure color are novel materials and are widely used in chemical and biological sensing. Combining PhCs with molecular imprinting technology (MIT), the molecularly imprinted photonic crystal (MIPC) sensors are fabricated, which can recognize the target molecules specifically. Besides the high sensitivity and selectivity, the MIPC sensors could realize the naked eye detection due to the optical properties. In this review, an overview of recent advances in sensing applications of MIPC sensors including the responsive mechanisms, application in environment monitoring and the application in human health is illustrated. The MIPC sensors all respond to the analytes specifically and also show high sensitivity in real samples, which provides a method to realize the rapid, convenient, naked eye and real-time detection. Furthermore, the current limitations and potential future directions of MIPC sensors are also discussed.